Electrodeposition of ZnNi Alloys from Ethylene Glycol/Choline Chloride Based Ionic Liquid. (30th August 2016) - Panzeri, Gabriele; Tresoldi, Matteo; Nobili, Luca; Magagnin, Luca
Abstract : Zinc alloys containing transition metals (Ni, Co and Fe) have attracted the attention because of their high corrosion resistance. In the framework of non-aqueous solution, improved deposit quality and process efficiency are expected with respect to aqueous ones. In this work, eutectic mixture of molar ratio 1 choline chloride: 4.5 ethylene glycol is considered. Codeposition of zinc and nickel is studied as a function of the metal salts concentration; particular attention is paid to the formation of Zn rich alloys (15-25 % wt. Ni).